2011
DOI: 10.1007/s12032-011-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of silibinin on migration and adhesion capacity of human highly metastatic breast cancer cell line, MDA-MB-231, by evaluation of β1-integrin and downstream molecules, Cdc42, Raf-1 and D4GDI

Abstract: Metastasis is a property of malignant cancer cells that requires integrins which with their downstream molecules participate in a number of signaling events in cells with pivotal roles in malignancy, migration and invasion of tumor cells. Silibinin, a flavonoid antioxidant from milk thistle (Silybum marianum L.), has attracted attention in the last decades for chemoprevention and chemotherapy of tumor cells. In the present study, the effect of silibinin on migration and adhesion capacity of MDA-MB-231 cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Silybin modulates imbalance in cellular homeostasis through interference with the expressions of cell-cycle regulators and proteins involved in apoptosis (15). Silybin also showed antiinflammatory (16) as well as antimetastatic activity (17), and synergistic effects with doxorubicin and cisplatin in both estrogen-dependent and independent human breast carcinoma cells (18). However, quantitative data on human breast tissue levels of silybin are absent, thus hampering the understanding of the biologic activities of this compound in breast cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Silybin modulates imbalance in cellular homeostasis through interference with the expressions of cell-cycle regulators and proteins involved in apoptosis (15). Silybin also showed antiinflammatory (16) as well as antimetastatic activity (17), and synergistic effects with doxorubicin and cisplatin in both estrogen-dependent and independent human breast carcinoma cells (18). However, quantitative data on human breast tissue levels of silybin are absent, thus hampering the understanding of the biologic activities of this compound in breast cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data are expressed as mean ±SD. .Moreover, in another study, Dastpeymanet al in 2012 showed significant dose-dependent inhibitory effect of silibinin on proliferation, migration and adhesion of MDA-MB-231 cells 14 . However, in this study, silibinin showed not only a dose-dependent but alsoa timedependent inhibitory effect on MDA-MB-231 cell proliferation.…”
Section: Effects Of Silibinin On Cell Proliferationmentioning
confidence: 91%
“…In the last decades silibininhas attracted attention for chemoprevention and chemotherapy of tumor cells. Silibinincanalso exert the significant anti-neoplastic effects in a variety of in vitro and in vivo epithelial cancer models, including breast, lung, skin, prostate, bladder, colon and kidney carcinomas 14,15 . In the present study, the effect of silibinin on expression of chemokine receptors CXCR3, CCR5 and CCR7 in MDA-MB-231 cells, a highly metastatic human breast cancer cell line, was investigated by Real-Time PCR.…”
Section: Introductionmentioning
confidence: 99%
“…After 5 min of crystal violet staining (0.1% (w/v) in 25% (v/v) methanol) at room temperature, the cells were gently rinsed five times with water to remove unbound stain and allowed to air-dry at room temperature. Fixed cells were lysed by 0.2% Triton X-100, and the absorbance was measured at 550 nm as follows: % Adhesion to matrix in 0 µM of DNC as 100 (Dastpeyman et al, 2012).…”
Section: Cell-matrix Adhesion Assaymentioning
confidence: 99%